Estudo fitoquímico aliado a uma análise quimiométrica e ensaios de atividade larvicida frente ao Aedes aegypti L. da espécie Waltheria viscosissima A. St.-Hil - Ferreira, Maria Denise Leite (2020)
Waltheria viscosissima A. St. Hil (Sterculiaceae), Malvaceae sensu lato, popularly known as "white mallow" and "viscous mallow" is an endemic species in Northeast Brazil, traditionally used as an antitussive, expectorant and anti-inflammatory. Considering the importance of research on species of the Malvaceae s.l. this study explores the phytochemical potential, combined with a chemometric analysis with multivariate data analysis models (PCA and PLS) and larvicidal activity against Ae. Aegypti of the species W. viscosissima. The isolation of the compounds was performed using chromatographic techniques and the structural elucidation was defined by 1D and 2D NMR. The study led to the identification of fourteen compounds from the aerial parts crude ethanolic extract, an alcohol (decanol), a mixture of steroids, a chlorophyll derivative, three triterpenes and seven flavonoids. The quantification of the compounds by spectrophotometric methods showed that the extract of the aerial parts had a high concentration of flavonoids, while the extract of the roots is rich in other phenolic compounds. In the antioxidant test against the DPPH radical, the aerial parts extract showed EC50 = 118,10 ± 1,21 µg/ml and the root extract EC50 = 77,32 ± 4,37 µg/ml, showing an interesting antioxidant potential. The extract of the roots and aerial parts of W. viscosissima showed larvicidal activity, being that of the root more potent compared to Ae. aegypti (LC50 = 4,78 mg /ml), being a favorable alternative to be used in an integrated control system for this vector. In the search to explore the possible mechanisms involved, in the larvicidal activity of the extracts, it was verified the possible alteration in the production of NO and mortality profile. In the larvae exposed to the extract of the aerial parts, a decrease in NO production was observed, in relation to the control, which may be one of the mechanisms of larval mortality. For the root extract, it is suggested that other mechanisms of action are involved in the triggered larvicidal activity. It was determined that time positively affects larvae survival, with the root extract showing a better mortality profile than the aerial parts extract. In addition, the hexane, ethyl acetate and hydroalcoholic phases of both extracts and some isolated substances were also evaluated against larvae in the fourth stage of Ae. aegypti, of these the hexane and ethyl acetate phases of the root and aerial parts showed the best activities with LC50 of 1,02, 0,83, 2,10 and 1,30 mg/ml, respectively. The compounds, betulonic acid and vitexin showed activity "in vitro" after 48 and 72 hours of exposure. In addition, a metabolic profile performed by 1H-NMR spectroscopy and multivariate data analysis was applied with the high, medium and low polarity phases of the extracts. Principal component analysis (PCA) with the spectra was able to distinguish the differences and metabolomic similarities between each part of the plant. The partial least squares regression (PLS) confirmed a strong correlation between the observed effects and the metabolic profiles of the species. The data show that mainly substances such as decanol, triterpenes and glycosylated flavones are the dominant compounds potentially associated with bioactivity against Ae. Aegypti. The results demonstrated the potential of 1H-NMR in the development of methodologies for predicting biological activities.